An overview of recent developments in China's metro systems. (May 2021) - Lin, Dong; Nelson, John D.; Beecroft, Mark; Cui, Jianqiang
Highlights: An overview of recent developments in China's metro systems is presented. The relationship between economic capabilities and metro development is discussed. The relationship between resident populations and metro development is examined. The relationship between administrative divisions and metro development is explored. Abstract: Along with rapid urbanisation and economic growth, massive development of transport infrastructure has been seen in China, facilitating overall economic development and improved quality of life. Metro is a common form of high-capacity public transport and urban underground space (UUS) utilisation in megacities. On many occasions, for social, environmental, economic and functional considerations a metro system is the optimal choice. China has seen remarkably rapid development of metro systems during the past two decades and is now leading the world with regard to the speed and scale of planning and construction of metro systems. This paper investigates recent developments in metro systems in mainland China, including the history of metro development, metro scale (measured by metro length, number of metro lines, number of metro stations, and metro patronage) and the relationships among three factors: economic capabilities, resident populations and administrative divisions of cities. The results show that China's cities with larger resident populations tend to develop larger-scale metro systems that are longer, with more metro lines and stations. With a higher Gross Domestic Product (GDP), a metro city in China tends to develop longer metro systems, and more extensive metro systems with more lines and more stations, carry more passengers. Cities at higher administrative levels, with greater economic strengths and larger populations, are more likely to develop more extensive metro networks.